1991
DOI: 10.1161/01.cir.83.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Clinical experience with the Palmaz-Schatz coronary stent. Initial results of a multicenter study.

Abstract: Stenting of native coronary arteries with a balloon-expandable stent was attempted in 226 patients after elective angioplasty. Delivery of the device was successful in 213 (94%) of the patients. Of these, 39 received aspirin and dipyridamole only (group 1) and 174 received aspirin, dipyridamole, and warfarin for 1-3 months (group 2). There was no abrupt closure (c1 day) or perioperative death in either group. In-hospital or perioperative complications in group 1 compared with group 2 were as follows: subacute … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
163
0
14

Year Published

1996
1996
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 556 publications
(187 citation statements)
references
References 31 publications
10
163
0
14
Order By: Relevance
“…For clinically defined stent thrombosis events, the associated 6-month mortality was 20.8%. These findings are consistent with the disastrous consequences of stent thrombosis reported in early studies 1,6,19,21,23,24 and are somewhat surprising because stent thrombosis events in our study patients were much more likely to occur while patients were still hospitalized. This is consistent, however, with a report by Hasdai et al 25 that showed poor clinical outcomes despite prompt restoration of blood flow after stent thrombosis.…”
Section: Cutlip Et Al Stent Thrombosissupporting
confidence: 93%
“…For clinically defined stent thrombosis events, the associated 6-month mortality was 20.8%. These findings are consistent with the disastrous consequences of stent thrombosis reported in early studies 1,6,19,21,23,24 and are somewhat surprising because stent thrombosis events in our study patients were much more likely to occur while patients were still hospitalized. This is consistent, however, with a report by Hasdai et al 25 that showed poor clinical outcomes despite prompt restoration of blood flow after stent thrombosis.…”
Section: Cutlip Et Al Stent Thrombosissupporting
confidence: 93%
“…The use of warfarin was found to significantly reduce rates of subacute occlusion (0.6%). 30 In this era, bleeding and vascular complications associated with the escalation of anticoagulant regimens significantly limited the use of PCI. In 1995, the importance of high-pressure post-dilation was recognized, informed by the use of intracoronary ultrasound, and this optimization of stent deployment allowed the use of less aggressive anticoagulation with aspirin and ticlopidine (replacing warfarin and dypyridamole).…”
Section: Evolution Of Percutaneous Interventionmentioning
confidence: 99%
“…[249,250]. This stent was subsequently modified to the Palmaz-Schatz stent, a heparin-coated stent [251][252][253]. The heparin-coated stent was superior to the BMS [254] but would ultimately be replaced by the drug eluting stent (DES).…”
Section: Intra-arterial Stentsmentioning
confidence: 99%